Zolpidem Dependency and Withdrawal Seizure: A Case Report Study - Haji Seyed Javadi, Seyed Alireza (Iran Red Crescent Med J, 2014)
INTRODUCTION: Zolpidem is a short acting inducer of sleep and thought to lack benzodiazepine properties such as anxiolysis, anticonvulsion, muscle relaxation and side effects such as dependency. Recently, some cases of Zolpidem abuse and dependency have been reported. In review of literature, we found that the lowest reported dosage of Zolpidem, which caused dependency, was 160 mg daily. CASE PRESENTATION: We reported a 30-year-old unmarried Iranian woman with dysthymic disorder and chronic insomnia treated with Zolpidem irregularly. She started to use Zolpidem with 5mg per day irregularly since a year ago but augmented its daily dosage gradually to 100 to 150 mg per day in divided doses. After a period of 16 hours without taking Zolpidem she developed a withdrawal syndrome, with generalized tonic-clonic seizures for two times. She was managed with supportive care and recovered completely. CONCLUSIONS: Zolpidem dependency and withdrawal seizure can occur with a dosage under last reported doses. Therefore, possibility of mentioned problems cannot be excluded at any dosage and physicians should pay more attention to potential of Zolpidem to create these adverse effects.